Hexagonal boron nitride aggregate particles and hexagonal boron nitride powder, resin composition, resin sheet

By using a specific manufacturing method in the hexagonal boron nitride powder to generate hexagonal boron nitride aggregated particles with small scale primary particles, the problems of dielectric strength and lightweight in the resin composition are solved, and the effects of high thermal conductivity and extremely high dielectric strength are achieved.

CN116419944BActive Publication Date: 2025-04-08TOKUYAMA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280007133.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-10
Filing Date
2022-03-01
Publication Date
2025-04-08
Estimated Expiration
2042-03-01

AI Technical Summary

Technical Problem

When the conventional hexagonal boron nitride powder is filled with a resin, it is difficult to achieve a resin composition with high dielectric strength and light weight, and there is a problem of anisotropy of heat conduction.

Method used

By adopting a specific manufacturing method, a reduction nitriding reaction is performed using an oxygen-containing boron compound, a carbon source and an oxygen-containing calcium compound to generate hexagonal boron nitride aggregated particles and powders with small scale primary particles, eliminating the anisotropy of heat conduction, and improving the dielectric strength and lightweight of the resin composition through the extremely small gap formed between the randomly oriented scaly primary particles.

Benefits of technology

High thermal conductivity and extremely high dielectric strength when filled into the resin are achieved, while reducing the density of the resin composition and achieving a lightweight effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116419944B_ABST
    Figure CN116419944B_ABST
Patent Text Reader

Abstract

[Subject] To provide hexagonal boron nitride aggregated particles and hexagonal boron nitride powder, which can impart extremely high dielectric strength and thermal conductivity to the resin composition obtained by filling the resin, and can reduce the density. [Solution] A hexagonal boron nitride aggregated particle, which is an aggregated particle of hexagonal boron nitride primary particles, wherein the major axis of the hexagonal boron nitride aggregated particles is 5 to 10 μm, the major axis / minor axis is 1.0 to 1.3, the circularity is in the range of 0.3 to 0.8, and the maximum diameter of the primary particles that can be confirmed on the surface of the aggregated particles according to the SEM observation image with a magnification of 10,000 times is 4 μm or less. A hexagonal boron nitride powder, which contains aggregated particles of hexagonal boron nitride primary particles, and the particle size distribution measured by the wet laser diffraction particle size distribution method has a cumulative volume frequency of 50% (D 50 ) is 5 to 150 μm, the volume-based median diameter of the pores measured by mercury intrusion porosimetry is less than 3.0 μm, and the content of impurity elements is less than 500 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to novel hexagonal boron nitride aggregated particles and hexagonal boron nitride powder and uses thereof. Specifically, the present invention provides hexagonal boron nitride aggregated particles and hexagonal boron nitride powder which can impart extremely high dielectric strength and thermal conductivity to a resin composition obtained by filling the resin and can reduce the density of the resin composition to make it lighter. Background Art

[0002] Hexagonal boron nitride powder is generally a white powder with a hexagonal layered structure similar to graphite, and has a variety of properties such as high thermal conductivity, high electrical insulation, high lubricity, corrosion resistance, mold release, high temperature stability, chemical stability, etc. Therefore, the resin composition filled with hexagonal boron nitride powder is suitable for use as a thermally conductive insulating sheet through molding.

[0003] In recent years, there has been an increasing demand for insulating sheets with low dielectric constants, low dielectric loss tangents, and high thermal conductivity for high-frequency devices, and there has been an increasing demand for hexagonal boron nitride powders with low dielectric constants compared to other high thermal conductive fillers such as aluminum nitride and aluminum oxide.

[0004] In particular, in the use as a low-specific-gravity thermally conductive insulating sheet for vehicles, hexagonal boron nitride powder, which has a low specific gravity compared to other high-thermal-conductive fillers such as aluminum nitride and aluminum oxide, has attracted attention.

[0005] The hexagonal boron nitride powder and the hexagonal boron nitride aggregated particles constituting the hexagonal boron nitride powder include primary particles formed of flaky particles derived from a crystal structure, and the flaky particles have thermal anisotropy. Therefore, when the boron nitride powder including the flaky particles as single particles is used as a thermally conductive insulating sheet as a filler, since the flaky particles are oriented along the surface direction of the thermally conductive insulating sheet, heat is transferred to the c-axis direction where the thermal conductivity of the flaky particles is low, and the thermal conductivity of the thermally conductive insulating sheet in the thickness direction is low.

[0006] In order to improve the thermal anisotropy of such hexagonal boron nitride particles having a scaly structure, a hexagonal boron nitride powder including aggregated particles in which scaly particles of hexagonal boron nitride are aggregated in random directions has been proposed.

[0007] For example, amorphous boron nitride powder is spray-granulated and reheated by spray drying, etc., to form aggregated particles formed by random orientation of flaky particles, or a mixed powder of amorphous boron nitride powder and additives such as oxides is press-formed and sintered to form a sintered body formed by random orientation of flaky particles (see patent document 1). Among these aggregated particles, the diameter of the flaky particles constituting the primary particles of the aggregation is large, and most of the primary particles have a size of more than 10 μm. Moreover, when the boron nitride powder formed by the above-mentioned aggregated particles is filled with resin, the resin is immersed in the pores between the primary particles as flaky particles, and the pores are buried, so that large bubbles are difficult to exist in the resin composition, thereby showing high dielectric strength.

[0008] However, there is still room for improvement about the above-mentioned dielectric strength. That is, when filled with resin, the resin easily immerses into large pores, but in the case of the central part of the aggregated particles, the gap becomes smaller or forms a continuous long gap, in the resin composition, there is a concern that the remaining gaps of the size that reduce the dielectric strength. Especially in the case of high viscosity of the resin, this tendency becomes significant. In addition, for the above-mentioned sintered body, in addition to the above-mentioned problems, there is also a concern that the inclusion of impurity elements as a sintering aid may cause the dielectric strength to decrease.

[0009] Furthermore, in the aggregated particles in which the voids are reduced by impregnating the resin into the pores in the aggregated particles, the specific gravity of the boron nitride powder in the resin composition is substantially equal to that of the bulk, and the weight reduction of the resin composition cannot be achieved.

[0010] In addition, the applicant proposed a hexagonal boron nitride powder having a maximum torque of 0.20 to 0.50 Nm, a DBP absorption of 50 to 100 ml / 100 g, and a tapped bulk density of 0.66 to 0.95 g / cm 3 (See Patent Document 2). The purpose of the invention described in the above patent document is to provide a hexagonal boron nitride powder that is easy to fill into resin, requires a small amount of solvent for varnishing, exhibits a high thermal conductivity when filled into resin, and has substantially no large pores that adversely affect the dielectric strength, and can impart high dielectric strength to the resin composition. However, the hexagonal boron nitride particles constituting the powder are densely aggregated, such that the particle size of the primary particles cannot be confirmed, and the lightweight caused by the formation of pores within the particles is expected to be further improved while improving the dielectric strength.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Publication No. 2017-165609

[0014] Patent Document 2: International Publication No. 2018-123571 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] Therefore, an object of the present invention is to provide hexagonal boron nitride aggregated particles and hexagonal boron nitride powder, wherein in the hexagonal boron nitride powder comprising aggregated particles formed by aggregation of scaly primary particles of hexagonal boron nitride, the anisotropy of thermal conduction is eliminated by aggregation, a high thermal conductivity is exhibited when filled with resin, and extremely high dielectric strength can be imparted to the resin composition obtained when filled with resin, thereby achieving the weight reduction of the above-mentioned resin composition.

[0017] Solutions for solving problems

[0018] The inventors of the present invention have conducted in-depth research to solve the above-mentioned problems. As a result, hexagonal boron nitride aggregated particles and hexagonal boron nitride powder are obtained by adopting a specific manufacturing method, wherein the manufacturing method is to use an oxygen-containing boron compound, a carbon source and an oxygen-containing calcium compound known as raw materials for obtaining boron nitride by a reduction nitridation method to carry out a reduction nitridation reaction, and the hexagonal boron nitride aggregated particles and hexagonal boron nitride powder eliminate the anisotropy of heat conduction by the aggregation of flaky primary particles, and by generating aggregated particles during the above-mentioned reaction, the flaky primary particles constituting the aggregated particles are small, so that since the gaps formed between the randomly oriented flaky primary particles are extremely small, when filled with resin, even if there are pores that are difficult for the resin to penetrate due to the above-mentioned gaps, the dielectric strength of the resin composition will not be reduced, and it can be ensured that the resin does not penetrate into the pores in the aggregated particles, thereby, the resin composition can also be lightweight, and it is confirmed that the above-mentioned problems can be completely eliminated, and the present invention has been completed.

[0019] That is, according to the present invention, there is provided a hexagonal boron nitride aggregated particle (hereinafter also referred to as specific hexagonal boron nitride aggregated particle), which is an aggregated particle of hexagonal boron nitride primary particles, wherein the major axis of the hexagonal boron nitride aggregated particle is 5 to 10 μm, the major axis / minor axis is 1.0 to 1.3, the circularity is in the range of 0.3 to 0.8, and the maximum diameter of the primary particles that can be confirmed on the surface of the aggregated particles according to the SEM observation image with a magnification of 10,000 times is 4 μm or less.

[0020] In addition, according to the present invention, there is provided a hexagonal boron nitride powder comprising aggregated particles of hexagonal boron nitride primary particles, wherein the particle size distribution measured by a wet laser diffraction particle size distribution method has a cumulative volume frequency of 50% (D 50 ) is 5 to 150 μm, the volume-based median diameter of the pores measured by mercury intrusion porosimetry is less than 3.0 μm, and the content of impurity elements is less than 500 ppm.

[0021] Furthermore, according to the present invention, there is provided a hexagonal boron nitride powder comprising the specific hexagonal boron nitride aggregated particles as aggregated particles of the hexagonal boron nitride primary particles.

[0022] The above hexagonal boron nitride powder preferably has a BET specific surface area of ​​1 to 15 m 2 / g, oil absorption is 50~190cc / 100g.

[0023] In addition, the specific hexagonal boron nitride aggregated particles of the present invention can be used together with the hexagonal boron nitride single particles without pores to form a thermally anisotropic hexagonal boron nitride powder covering the single particles without reducing the dielectric strength. That is, according to the present invention, there is provided a hexagonal boron nitride powder comprising hexagonal boron nitride single particles and specific hexagonal boron nitride aggregated particles, wherein the content ratio of the specific hexagonal boron nitride aggregated particles is 5% or more, and the particle size (D 50 ) is 5 to 150 μm.

[0024] Furthermore, the present invention provides a resin composition having excellent thermal conductivity and high dielectric strength, which is obtained by filling the boron nitride powder as a filler, and a resin sheet formed from the resin composition.

[0025] Effects of the Invention

[0026] The specific hexagonal boron nitride aggregated particles of the present invention are composed of aggregated particles of fine hexagonal boron nitride scaly primary particles, and play an effect of eliminating the anisotropy of thermal conductivity caused by aggregation. Furthermore, on the basis of the above characteristics, by having fine pores on the surface of the aggregated particles, excellent characteristics that existing aggregates do not have are played. That is, since the primary particles constituting the specific hexagonal boron nitride aggregated particles of the present invention are fine, the gaps between the particles are extremely small, and unlike the gaps between the existing plate-like aggregated particles, the voids present in the above gaps when filled with resin have little effect on the dielectric strength.

[0027] The hexagonal boron nitride powder of the present invention is composed of aggregated particles of flaky primary particles of fine hexagonal boron nitride, and therefore, the anisotropy of thermal conductivity caused by aggregation can be eliminated. Furthermore, on the basis of the above characteristics, by having a structure in which the above-mentioned fine hexagonal boron nitride primary particles are densely aggregated, fine pores are formed on the surface of the aggregated particles, and excellent characteristics that are not available in existing aggregates are exerted. That is, the aggregated particles of the primary particles constituting the hexagonal boron nitride powder of the present invention are as described above, and the voids existing in the above gaps when filled with resin have little effect on the dielectric strength.

[0028] Therefore, the resin composition filled with the above-mentioned hexagonal boron nitride powder or the hexagonal boron nitride powder containing the above-mentioned specific hexagonal boron nitride aggregated particles can exert extremely high dielectric strength. In addition, the above-mentioned gaps existing in the aggregated particles can also achieve the weight reduction of the hexagonal boron nitride powder and further achieve the weight reduction of the resin composition filled with the hexagonal boron nitride powder.

[0029] In addition, the specific hexagonal boron nitride aggregated particles and hexagonal boron nitride powder of the present invention can be produced without using a sintering method that requires a sintering aid, have a low content of impurity elements, and can be highly purified, thereby maximally suppressing the reduction in the dielectric strength of the aforementioned resin composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM photograph of specific aggregated particles in the hexagonal boron nitride powder obtained in Example A1.

[0031] Figure 2 This is a SEM photograph of the hexagonal boron nitride powder obtained in Example A1.

[0032] Figure 3 This is a SEM photograph of the surface of coarse aggregated particles of the hexagonal boron nitride powder obtained in Example A1. DETAILED DESCRIPTION

[0033] (Specific hexagonal boron nitride aggregate particles)

[0034] The specific hexagonal boron nitride aggregated particles of the present invention are aggregated particles of hexagonal boron nitride primary particles, with a major diameter of 5 to 10 μm, a major diameter / minor diameter of 1.0 to 1.3, a circularity in the range of 0.3 to 0.8, and a maximum diameter of primary particles that can be confirmed on the surface of the aggregated particles according to an SEM observation image with a magnification of 10,000 times is 4 μm or less.

[0035] It should be noted that the identification of hexagonal boron nitride is to confirm that the sample powder has no peaks other than hexagonal boron nitride in the X-ray diffraction measurement, and is identified as hexagonal boron nitride powder. Here, the above-mentioned X-ray diffraction measurement uses the fully automatic horizontal multi-purpose X-ray diffractometer SmartLab (trade name) manufactured by Rigaku. The measurement conditions are set to a scanning speed of 20 degrees / minute, a step width of 0.02 degrees, and a scanning range of 10 to 90 degrees. In addition, the GI value representing the crystallinity of the hexagonal boron nitride powder is calculated by the integrated intensity ratio (area ratio) of the (100), (101) and (102) diffraction lines of the X-ray diffraction spectrum of the hexagonal boron nitride powder according to the formula GI = [{(100) + (101)} / [(102)]. The GI value of the hexagonal boron nitride powder is less than 2.5, which is also confirmed in the specific hexagonal boron nitride aggregated particles obtained in the example.

[0036] The specific hexagonal boron nitride aggregated particles of the present invention include aggregates of scaly primary particles of hexagonal boron nitride. However, the above-mentioned aggregates are not prepared by aggregating scaly hexagonal boron nitride single particles manufactured at one time as in the existing granulation method and sintering method, but are obtained by adopting specific reaction conditions for synthesizing hexagonal boron nitride, and aggregated particles can be generated during the reaction.

[0037] Therefore, the specific hexagonal boron nitride aggregated particles of the present invention are composed of flaky primary particles of fine hexagonal boron nitride, and the maximum diameter of the primary particles that can be confirmed on the surface of the aggregated particles according to the SEM observation image with a magnification of 10,000 times is less than 4 μm, and is particularly composed of extremely small primary particles of less than 3 μm. And thus, the gaps in the aggregated particles are extremely small, and the voids present in the above-mentioned gaps when filled with resin have basically no effect on the dielectric strength, and the obtained resin composition can exert extremely high dielectric strength. In addition, the holes (gaps) are present in and on the surface of the aggregated particles, so that the lightweight of the resin composition obtained by filling the hexagonal boron nitride powder can also be achieved.

[0038] The specific hexagonal boron nitride aggregated particles of the present invention have a major diameter of 5 to 10 μm, a major diameter / minor diameter of 1.0 to 1.3, and a circularity in the range of 0.3 to 0.8. However, when mixed with other hexagonal boron nitride particles in a resin composition, the particles have excellent fluidity and an improved effect on the filling property of the resin, which is effective in improving the thermal conductivity of the resin composition.

[0039] It should be noted that the major diameter and minor diameter are calculated from the SEM observation image at a magnification of 10,000 times. In addition, the circularity is calculated by using image analysis software on the SEM observation image at a magnification of 10,000 times, based on 4π×(area) / (circumference) 2 's formula and find it.

[0040] According to the manufacturing method described later, it is difficult to manufacture a pure powder consisting only of the specific hexagonal boron nitride aggregated particles of the present invention, and aggregated particles having various shapes and sizes are generated. Therefore, it is preferably used as a powder in which the content ratio of the specific hexagonal boron nitride aggregated particles is increased by removing coarse particles and fine particles by classification or the like.

[0041] As described above, for the specific hexagonal boron nitride aggregated particles of the present invention, although the median particle size of the pores cannot be selectively measured, it is confirmed that the aggregated particles constituting the hexagonal boron nitride powder obtained by the manufacturing method described later have the same pore structure caused by the dense aggregation of fine primary particles. Therefore, the pore size of the above-mentioned hexagonal boron nitride powder can be measured to determine the median particle size of the pores of the specific hexagonal boron nitride aggregated particles. In the present invention, the median particle size of the pores of the above-mentioned specific hexagonal boron nitride aggregated particles is preferably less than 3.0 μm, preferably 2.8 μm, and further preferably less than 2.5 μm. Similarly, for the specific hexagonal boron nitride aggregated particles of the present invention, the pore volume of the pores in the range of pore diameters of less than 3 μm is preferably 0.5 cm 3 / g or more, preferably 0.5 to 2.0 cm 3 / g.

[0042] The pore volume-based median diameter and pore volume are calculated from cumulative pore distribution obtained by measuring pores of 0.0036 μm to 200 μm using mercury intrusion porosimetry using Autopore IV9520 manufactured by Micromeritics, with pore diameters plotted on the horizontal axis and cumulative pore volumes plotted on the vertical axis.

[0043] The specific hexagonal boron nitride aggregated particles of the present invention are obtained by a method without using a sintering aid in the manufacturing method described later, and therefore, there is no purity reduction caused by the sintering aid, and the purity is high. For example, when used as a filler in a resin composition constituting an insulating sheet, it works together with the effect of the aforementioned small pores to improve the withstand voltage. That is, the content of impurity elements in the specific hexagonal boron nitride aggregated particles of the present invention is preferably 500 ppm or less, and particularly preferably 400 ppm or less.

[0044] The impurity elements mentioned here are calcium, magnesium, sodium, aluminum, lithium, strontium, iron, sulfur, nickel, chromium, manganese, silicon, phosphorus, titanium, barium, and cobalt. The content of the impurity elements mentioned above refers to the total content of the impurity elements mentioned above.

[0045] The impurity element content ratio of the hexagonal boron nitride aggregate particles is a value obtained by measuring the hexagonal boron nitride powder obtained by the production described below by fluorescent X-ray analysis. In the examples, ZSX Primus2 (trade name) manufactured by Rigaku Corporation was used as the fluorescent X-ray analyzer.

[0046] When the C% of the specific hexagonal boron nitride aggregated particles of the present invention is 0.04% or less and the O% is 0.4% or less, it is more effective in improving the thermal conductivity and dielectric strength in addition to the small amount of impurity elements mentioned above.

[0047] The O% of the specific hexagonal boron nitride aggregate particles was measured using an oxygen / nitrogen analyzer EMGA-620 manufactured by Horiba, Ltd. The C% of the hexagonal boron nitride powder was measured using EMIA-110 manufactured by Horiba, Ltd.

[0048] (Hexagonal Boron Nitride Powder)

[0049] The hexagonal boron nitride powder of the present invention is characterized in that it comprises aggregated particles of hexagonal boron nitride primary particles, has a pore volume-based median diameter of 3 μm or less, and contains impurity elements of 500 ppm or less.

[0050] It should be noted that the identification of hexagonal boron nitride is the same as that of the above-mentioned specific hexagonal boron nitride aggregated particles, that is, confirming that the sample powder has no peaks other than hexagonal boron nitride in the X-ray diffraction measurement, and identifying it as hexagonal boron nitride powder. Here, the above-mentioned X-ray diffraction measurement is the same as that of the specific hexagonal boron nitride aggregated particles, and the GI value of the hexagonal boron nitride powder of the present invention is 2.5 or less, which is also confirmed in the examples.

[0051] The hexagonal boron nitride powder of the present invention contains aggregates of scaly primary particles of hexagonal boron nitride, but the above-mentioned aggregates are not prepared by aggregating scaly hexagonal boron nitride single particles manufactured at one time as in the existing granulation method and sintering method, but are obtained by using specific reaction conditions for synthesizing hexagonal boron nitride to generate aggregated particles.

[0052] Therefore, the aggregated particles constituting the hexagonal boron nitride powder of the present invention are composed of fine scaly primary particles of hexagonal boron nitride, and the gaps between the aggregated particles are extremely small, showing a characteristic value of a volume-based median particle size of pores of less than 3.0 μm. The above-mentioned volume-based median particle size is preferably 2.8 μm, and more preferably less than 2.5 μm. In the case where the above-mentioned volume-based median particle size of the pores exceeds 3.0 μm, bubbles that affect the insulation resistance become easy to remain when filled with resin, and it is difficult to exert high dielectric strength. That is, the volume-based median particle size of the pores of the aggregated particles constituting the hexagonal boron nitride powder of the present invention shows the aforementioned value, so that the voids present in the gaps when filled with resin have basically no effect on the dielectric strength, and the obtained resin composition can exert extremely high dielectric strength. In addition, the presence of pores (gaps) in and on the surface of the aggregated particles can also achieve lightweight resin compositions obtained by filling hexagonal boron nitride powder. The above-mentioned pores can be made of Figure 3 The SEM pictures confirmed.

[0053] The hexagonal boron nitride powder of the present invention has a pore volume of 0.2 cm2 in the range of pores with a pore diameter of 3 μm or less, excluding the volume-based median diameter of the pores of the aggregated particles. 3 / g or more, preferably 0.5 to 2.0 cm 3 / g is preferred because the effect of reducing the weight of the resin composition due to the remaining pores is further enhanced.

[0054] The pore volume-based median diameter and pore volume were measured by mercury intrusion porosimetry using Autopore IV9520 manufactured by Shimadzu Corporation for pores of 0.0036 μm to 200 μm, and calculated from a cumulative pore distribution obtained by plotting the pore diameter on the horizontal axis and the cumulative pore volume on the vertical axis.

[0055] The hexagonal boron nitride powder of the present invention is obtained by a method without using a sintering aid in the production method described below, and therefore has high purity without a decrease in purity due to a sintering aid. For example, when used as a filler in a resin composition constituting an insulating sheet, it works together with the effect of the aforementioned small pores to improve the withstand voltage. That is, the hexagonal boron nitride powder of the present invention is characterized in that the content of impurity elements is 500 ppm or less, particularly 400 ppm or less, and has high purity.

[0056] Here, the impurity elements mentioned herein include the same ones as those mentioned above for the specific hexagonal boron nitride aggregated particles, and the content of the impurity elements mentioned above refers to the total content of the impurity elements mentioned above.

[0057] The impurity element content ratio of the hexagonal boron nitride powder is measured in the same manner as that of the specific hexagonal boron nitride aggregate particles.

[0058] When the C% of the hexagonal boron nitride powder of the present invention is 0.04% or less and the O% is 0.4% or less, it is more effective in improving the thermal conductivity and dielectric strength in conjunction with the small amount of impurity elements.

[0059] The 0% of the hexagonal boron nitride powder is measured in the same manner as in the specific hexagonal boron nitride aggregate particles.

[0060] The particle size of the hexagonal boron nitride powder of the present invention also includes the case of mixed hexagonal boron nitride powder described later. If the filling property into the resin is taken into consideration, the particle size distribution in the wet laser diffraction particle size distribution method is preferably a particle size at which the cumulative volume frequency is 50% (D 50 ) is 5 to 150 μm, preferably 10 to 100 μm, and particularly 20 to 80 μm. In order to adjust the particle size to the above, the coarse aggregated particles, specifically aggregated particles exceeding 200 μm, particularly exceeding 150 μm, are classified by a sieving method or the like from the coarse hexagonal boron nitride powder obtained by the manufacturing method described later, and the hexagonal boron nitride powder of the present invention can also be formed. In addition, the hexagonal boron nitride powder can also be formed by separating the coarse particles and crushing them into appropriate sizes and returning them to the hexagonal boron nitride powder.

[0061] In addition, in the examples, the measurement of the particle size by the wet laser diffraction particle size distribution method was performed using LA-950V2 (trade name) manufactured by HORIBA Corporation.

[0062] In addition, the specific surface area of ​​the hexagonal boron nitride powder of the present invention is preferably 1 to 15 m 2 / g, if 1.5~14.0m 2 / g is more preferably 2.0 to 13.0 m 2 / g is more preferred. That is, more than 15.0m 2 / g of hexagonal boron nitride powder means that it contains a large number of fine particles. In such hexagonal boron nitride powder, the content of low-crystalline boron nitride powder increases, which not only causes thermal resistance in the insulating heat sink, but also is not preferred from the perspective of operability such as the powder flying easily. On the other hand, less than 1m 2 In the hexagonal boron nitride powder of 1000 g / g, the ratio of flat hexagonal boron nitride single particles with grown crystals increases, which is not preferable because of the anisotropy of thermal conductivity and there is a concern that the thermal conductivity of the resin composition when filled with resin may decrease.

[0063] The specific surface area of ​​the hexagonal boron nitride powder is a value measured by the BET one-point method, and in the Examples, the specific surface area was measured using Macsorb HM model-1201 (trade name) manufactured by Mountech Corporation.

[0064] In addition, the oil absorption of the hexagonal boron nitride powder of the present invention is preferably 50 to 190 ml / 100 g, particularly preferably 55 to 170 ml / 100 g, and further preferably 60 to 150 ml / 100 g. That is, the DBP absorption is a characteristic of the hexagonal boron nitride powder that indicates the amount of open pores in the aggregated particles, the state of the presence or absence of a structure on the particle surface, and the wettability with the resin. The more open pores there are and the more developed the structure is, the higher the DBP absorption is. That is, when the oil absorption is too low, the open pores are large and the structure is not sufficiently developed, which is not preferred. When the oil absorption is too high, the opposite tendency occurs, and it is easy to bite large bubbles when the resin composition is made, so it is not preferred. It should be noted that in the hexagonal boron nitride powder of the present invention, since the aggregated particles constituting it contain extremely fine primary particles, even if the structure is developed, the open pores formed thereby are small, and it will not be a problem when the resin composition is made.

[0065] The oil absorption of the hexagonal boron nitride powder is measured based on the procedure described in JIS K5101-13-1:2004 ("Testing Methods for Pigments" - Part 13: Oil Absorption - Section 1: Purified Linseed Oil Method).

[0066] Furthermore, the hexagonal boron nitride powder of the present invention preferably has a tapped bulk density of 0.40 g / cm 3More than. That is, the tapped bulk density is an indicator of the particle shape and particle size distribution width in the characteristics of the hexagonal boron nitride powder. When the above value is high, it means that there are fewer large open pores, more aggregated particles close to spherical shapes, and a state of particle size distribution close to the densest packing. Moreover, the hexagonal boron nitride powder of the present invention can improve the tapped bulk density by increasing the content of the specific hexagonal boron nitride aggregated particles described later, thereby facilitating the filling of gaps in the powder. It should be noted that the tapped bulk density of the hexagonal boron nitride powder prepared in the examples is all 0.40 g / cm 3 above.

[0067] The hexagonal boron nitride powder of the present invention is preferably a scheme that contains aggregated particles of hexagonal boron nitride primary particles with a major diameter of 5 to 10 μm, a major diameter / minor diameter of 1.0 to 1.3, and a roundness in the range of 0.3 to 0.8 at a ratio of 5% or more, preferably 10% or more (hereinafter also referred to as spherical hexagonal boron nitride aggregated particles). The most suitable spherical hexagonal boron nitride aggregated particles are the aforementioned specific hexagonal boron nitride aggregated particles. That is, as understood from the manufacturing method described later, the specific hexagonal boron nitride aggregated particles are obtained as a hexagonal boron nitride powder containing hexagonal boron nitride aggregated particles inevitably generated in the reaction, and the hexagonal boron nitride aggregated particles constituting the above-mentioned powder have a structure in which fine primary particles are densely aggregated. Therefore, when specific hexagonal boron nitride particles are included as spherical hexagonal boron nitride aggregated particles, it can be said that it is most preferred in terms of satisfying the characteristics of the hexagonal boron nitride powder of the present invention.

[0068] It should be noted that, as long as the above-mentioned characteristics of the hexagonal boron nitride powder of the present invention are satisfied and the above-mentioned major diameter, ratio, and circularity are satisfied, spherical hexagonal boron nitride aggregated particles other than the above-mentioned specific hexagonal boron nitride aggregated particles may be used.

[0069] In addition, the major axis, major axis / minor axis, and circularity were confirmed and determined using a SEM observation image at a magnification of 10,000 times, similarly to the above-mentioned specific hexagonal boron nitride aggregated particles.

[0070] The hexagonal boron nitride powder of the present invention may be mixed with hexagonal boron nitride powder containing other hexagonal boron nitride particles within the range satisfying the above-mentioned characteristics. The powder mixed with other hexagonal boron nitride particles is also referred to as "mixed hexagonal boron nitride powder".

[0071] The mixed hexagonal boron nitride powder contains specific hexagonal boron nitride aggregated particles and other hexagonal boron nitride particles, and the content ratio of the specific hexagonal boron nitride aggregated particles is preferably 5% or more, preferably 10% or more, and more preferably 20% or more.

[0072] In the present invention, the other hexagonal boron nitride powder to be mixed is not particularly limited as long as it does not affect the characteristics of the hexagonal boron nitride of the present invention. It is suitable to include a powder of hexagonal boron nitride single particles that can suppress the occurrence of voids after filling into the resin. The above-mentioned hexagonal boron nitride single particles are usually flat in shape and have anisotropy of thermal conductivity. However, when filled into the resin, they can eliminate the above anisotropy and exert excellent thermal conductivity by contacting with aggregated particles of hexagonal boron nitride primary particles, especially specific hexagonal boron nitride aggregated particles.

[0073] As the above-mentioned hexagonal boron nitride single particles, it is preferred that the aspect ratio of the particles (ratio of the major diameter to the thickness of the particles (major diameter / thickness) is 3 to 20, and the major diameter is 1 to 30 μm. In addition, hexagonal boron nitride aggregated particles other than the specific hexagonal boron nitride aggregated particles may be used in combination within a range that does not significantly hinder the effect of the present invention produced by the specific hexagonal boron nitride aggregated particles.

[0074] The hexagonal boron nitride powder of the present invention also includes the case of mixed hexagonal boron nitride powder. The spherical hexagonal boron nitride aggregated particles represented by the aforementioned specific hexagonal boron nitride aggregated particles have an appropriate size suitable for filling the gaps between other aggregated particles. In addition, they are roughly spherical. Therefore, it is estimated that by existing in the hexagonal boron nitride powder at the aforementioned ratio, the filling property of the hexagonal boron nitride powder into the resin can be improved, the residue of larger bubbles can be effectively suppressed, and it is beneficial to improve the dielectric strength of the resin composition.

[0075] The greater the ratio of the spherical hexagonal boron nitride aggregated particles in the hexagonal boron nitride powder is than the aforementioned lower limit value, the more favorable it is for the above-mentioned effect. Therefore, it is preferred that, in the case of specific hexagonal boron nitride aggregated particles, the hexagonal boron nitride powder obtained by the manufacturing method described later utilizes the aforementioned classification based on a sieve, etc. to classify particles with larger particle sizes, thereby increasing their ratio.

[0076] In addition, the above-mentioned specific hexagonal boron nitride aggregated particles are generated as a part of the hexagonal boron nitride powder by the manufacturing method described later, but the size of the hexagonal boron nitride primary particles constituting the aggregated particles is small and consistent compared with other aggregated particles, and has the characteristic that the major diameter of almost all primary particles is less than 4 μm. The above-mentioned characteristics are also beneficial to improving the dielectric strength in the above-mentioned resin composition.

[0077] It should be noted that, in the present invention, the content ratio (%) of spherical hexagonal boron nitride aggregated particles in the hexagonal boron nitride powder also includes the case of specific hexagonal boron nitride aggregated particles, which can be obtained by the following method. First, using the dry vibrating screen KFC-500-1D of KOWA Corporation, using a SUS sieve with an aperture of 45μm, the hexagonal boron nitride powder is sieved on the 45μm sieve for 30 minutes, and the weight ratio of the 45μm sieve is obtained. X%. After that, based on the SEM observation image of the recovered 45μm sieve product at a magnification of 500 times, spherical hexagonal boron nitride aggregated particles such as specific hexagonal boron nitride aggregated particles and particles other than them are screened, and the SEM observation image area ratio Y% of the spherical hexagonal boron nitride aggregated particles under the 45μm sieve is obtained. Finally, the ratio (X×Y×0.01)% obtained by multiplying the weight ratio X% under the 45μm sieve by the SEM observation image area ratio Y% of the hexagonal boron nitride aggregated particles under the 45μm sieve is used as the spherical hexagonal boron nitride aggregated particle ratio in the present invention. For example, if the weight ratio X under the 45μm sieve of the hexagonal boron nitride powder is 20wt% and the SEM observation image area ratio Y of the spherical hexagonal boron nitride aggregated particles under the 45μm sieve is 60%, then the spherical hexagonal boron nitride aggregated particle ratio Z is calculated to be 20×60×0.01=12%.

[0078] In the hexagonal boron nitride powder of the present invention, the median particle size of the pores of the mixed hexagonal boron nitride powder containing the specific hexagonal boron nitride aggregated particles and other hexagonal boron nitride particles is preferably 3.0 μm or less, preferably 2.8 μm or less, and more preferably 2.5 μm or less, similarly to the specific hexagonal boron nitride aggregated particles. In addition, the pore volume of the pores in the range of pore diameter of 3 μm or less in the above-mentioned hexagonal boron nitride powder is preferably 0.5 cm 3 / g or more, preferably 0.5 to 2.0 cm 3 As described above, in order to maintain the characteristics of specific hexagonal boron nitride aggregate particles, the other hexagonal boron nitride particles in the hexagonal boron nitride powder are preferably single particles.

[0079] The pore volume-based median diameter and pore volume can be measured in the same manner as in the specific hexagonal boron nitride aggregate particles.

[0080] (Method for producing boron nitride powder)

[0081] The method for producing the specific hexagonal boron nitride aggregate particles and hexagonal boron nitride powder of the present invention is not particularly limited. If a representative production method is exemplified, the following production method can be cited: an oxygen-containing boron compound having a residual component on a 425 μm sieve of less than 3% by mass, a carbon source, and an oxygen-containing calcium compound are mixed at a ratio B / C (element ratio) of 0.63 to 0.73 calculated as the B source contained in the oxygen-containing boron compound and the C source contained in the carbon source, and 4 to 12 parts by mass of the oxygen-containing calcium compound calculated as CaO relative to 100 parts by mass of the total amount of the oxygen-containing boron compound and the carbon source (B2O3, C conversion value). The mixture is heated to a maximum temperature of 1910 to 2000°C in a nitrogen atmosphere, and after reduction nitridation is performed, by-products other than boron nitride present in the reaction product are removed by pickling.

[0082] (raw material)

[0083] The most significant feature of the production method of the present invention is that the oxygen-containing boron compound, carbon source, and oxygen-containing calcium compound as raw materials with controlled particle sizes are mixed at a predetermined ratio as described below, and reduction nitridation is performed at a high temperature of 1910° C. or higher. The effects of each raw material are as follows.

[0084] (Oxygen-containing boron compounds)

[0085] In the manufacturing method of the present invention described above, as the raw material of the oxygen-containing boron compound, a compound containing a boron atom can be used without limitation. For example, boric acid, boric anhydride, metaboric acid, perboric acid, subboric acid, sodium tetraborate, sodium perborate, etc. can be used. Boric acid and boron oxide that are easily available are usually suitable. In addition, the average particle size of the oxygen-containing boron compound used is set to preferably 3% by mass or less of the residual component on the 425μm sieve, preferably 1.5% by mass or less. In particular, it is more preferred that the residual component on the 300μm sieve is 50% or less, and it is further preferred that the residual component on the 250μm sieve is 70% or less. That is, if the residual component on the 425μm sieve of the oxygen-containing boron compound is 3% or more by mass, the coarse boron nitride aggregated particles of 150μm or more become easy to remain, the residual pores in the coarse aggregated particles increase, and the median particle size of the pores in the obtained hexagonal boron nitride powder exceeds 3μm, resulting in a decrease in dielectric strength.

[0086] (Calcium Oxygen Compounds)

[0087] The oxygen-containing calcium compound forms a composite oxide with the oxygen-containing boron compound to form a composite oxide having a high melting point, and has a function of preventing the oxygen-containing boron compound from volatilizing.

[0088] In the manufacturing method of the present invention, the oxygen-containing calcium compound used as the catalyst and the anti-evaporation agent of the oxygen-containing boron compound can be used without particular limitation. It is particularly suitable to use an oxygen-containing calcium compound containing oxygen and calcium. As the oxygen-containing calcium compound, for example, calcium carbonate, calcium hydrogen carbonate, calcium hydroxide, calcium oxide, calcium nitrate, calcium sulfate, calcium phosphate, calcium oxalate, etc. can be cited. It is also possible to mix these two or more and use them. Among them, calcium oxide and calcium carbonate are preferably used.

[0089] The above-mentioned oxygen-containing calcium compound may be used in combination of two or more thereof. The average particle size of the above-mentioned oxygen-containing calcium compound is preferably 0.01 to 200 μm, more preferably 0.05 to 120 μm, and particularly preferably 0.1 to 80 μm.

[0090] (Carbon Source)

[0091] In the manufacturing method of the present invention, as a carbon source, a known carbon material that acts as a reducing agent can be used without particular limitation. For example, in addition to amorphous carbon such as carbon black, activated carbon, and carbon fiber, crystalline carbon such as diamond, graphite, and nanocarbon, and pyrolytic carbon obtained by thermal cracking of monomers or polymers can also be cited. Among them, amorphous carbon with high reactivity is preferred, and further, carbon black is particularly suitable for use in terms of industrial quality control. In addition, as the above-mentioned carbon black, acetylene black, furnace black, thermal cracking carbon black, etc. can be used. In addition, the average particle size of the above-mentioned carbon source is preferably 0.01 to 5 μm, more preferably 0.02 to 4 μm, and particularly preferably 0.05 to 3 μm. That is, by making the average particle size of the carbon source less than 5 μm, the reactivity of the carbon source becomes high, and by setting it to more than 0.01 μm, the operation becomes easy.

[0092] In the production method of the present invention, the form in which the mixture containing the above-mentioned raw materials is supplied to the reaction is not particularly limited, and the mixture may be directly in a powder form or may be formed into granules.

[0093] In the production method of the present invention, the method for mixing the raw materials is not particularly limited, and a common mixer such as a vibration mill, a bead mill, a ball mill, a Henschel mixer, a tumble mixer, a vibration stirrer, or a V-shaped mixer can be used.

[0094] The granulation method may be carried out by a known method such as extrusion granulation, tumbling granulation, granulation by rolling, etc. using a binder as needed. In this case, the size of the granules is preferably about 5 to 10 mm.

[0095] (Preparation of Raw Materials)

[0096] In the present invention, the reduction nitridation reaction is carried out by supplying a carbon source and nitrogen, but in order to effectively obtain the target hexagonal boron nitride aggregated particles, the ratio of the B source to the carbon source contained in the oxygen-containing boron compound needs to be set to 0.63 to 0.73, preferably 0.65 to 0.72 in terms of B / C (element ratio). That is, if the molar ratio exceeds 0.73, the ratio of the boron compound that is volatilized without reduction increases, and it is easy to form a composite oxide with the Ca additive, and the melting point of the above-mentioned composite oxide is low, and the plate-like particles are easy to grow grains, and it is difficult to obtain the target primary particles with a small particle size and aggregated particles with holes. In addition, when the molar ratio is lower than 0.63, the carbon content ratio is high, and there is a concern that impurities from the carbon source will remain.

[0097] In the present invention, in order to effectively obtain the target hexagonal boron nitride aggregated particles, it is necessary to mix the oxygen-containing calcium compound at a ratio of 4 to 12 parts by mass in terms of CaO conversion relative to 100 parts by mass of the total amount of the oxygen-containing boron compound and the carbon source (B2O3, C conversion value). At this time, when the CaO conversion mass part is less than 4 parts by mass, the ratio of the boron compound that is volatilized without reduction increases, not only the yield is reduced, but also the melting point of the CaO-B2O3 composite oxide formed with the residual boron compound decreases, promoting the grain growth of the hexagonal boron nitride particles, and it is difficult to form aggregated particles with target pores, so it is not preferred. When the CaO conversion mass part is more than 12 parts by mass, there is a concern that impurities derived from calcium will remain, which is not preferred.

[0098] In the present invention, by adjusting the particle size and composition ratio of the raw materials, it is possible to produce aggregated particles having a small primary particle size with high selectivity without causing excessive targeted grain growth.

[0099] (Reductive nitridation)

[0100] In the method for producing boron nitride of the present invention, the supply of nitrogen source to the reaction system can be formed by known means. For example, the most common method is to circulate nitrogen gas in the reaction system of the reaction apparatus exemplified below. In addition, the nitrogen source used is not limited to the above-mentioned nitrogen gas, and there is no particular restriction as long as it is a gas that can be nitrided in the reduction nitridation reaction. Specifically, in addition to the above-mentioned nitrogen gas, ammonia gas can also be used. In addition, a gas obtained by mixing non-oxidizing gases such as hydrogen, argon, and helium with nitrogen and ammonia gas can also be used.

[0101] In the above-mentioned manufacturing method, in order to obtain a hexagonal boron nitride powder with high crystallinity and pores, the heating temperature in the reduction nitridation reaction usually needs to be 1910°C to 2000°C, preferably 1920°C to 1980°C. By setting the heating temperature to 1910°C to 2000°C, the crystallinity of the hexagonal boron nitride particles is improved, the outer periphery of the primary particle shape becomes sharper, and the effect of increasing the tiny pores between the particles is achieved. In addition, when the above-mentioned temperature is lower than 1910°C, the reduction nitridation reaction does not proceed, and it is difficult to obtain white hexagonal boron nitride with high crystallinity. At a temperature exceeding 2000°C, the effect reaches a maximum, which is not only economically disadvantageous, but also increases damage to the heating furnace, which is not preferred.

[0102] The time for the reduction nitridation reaction can be appropriately determined, and is usually about 6 to 30 hours.

[0103] The above manufacturing method can be carried out using a known reaction device capable of controlling the reaction atmosphere. For example, an atmosphere-controlled high-temperature furnace using high-frequency induction heating or heater heating can be used. In addition to intermittent furnaces, continuous furnaces such as pusher-type tunnel furnaces and vertical reaction furnaces can also be used.

[0104] (Pickling)

[0105] In the manufacturing method of the present invention, the reaction product obtained by the above-mentioned reduction nitridation contains impurities such as a composite oxide containing boron oxide-calcium oxide in addition to hexagonal boron nitride, so it is preferably washed with acid. The above-mentioned acid washing method is not particularly limited, and a known method can be adopted without restriction. For example, the following method can be cited: the boron nitride containing by-products obtained after the nitridation treatment is crushed and put into a container, and 5 to 10 times the amount of dilute hydrochloric acid (5 to 20 mass % HCl) of the hexagonal boron nitride powder containing the impurities is added to contact it for 4 to 8 hours.

[0106] As the acid used in the pickling, in addition to hydrochloric acid, nitric acid, sulfuric acid, acetic acid, etc. can be used.

[0107] After the pickling, pure water is used to wash away the residual acid. As the method for the washing, the acid used in the pickling is filtered, and then the acid-washed boron nitride is dispersed in pure water in an amount equal to that of the acid used, and filtered again.

[0108] (dry)

[0109] The conditions for drying the water-containing cake after the acid washing and water washing are preferably drying in air or under reduced pressure at 50 to 250° C. The drying time is not particularly specified, but it is preferred to dry until the water content is as close to 0% as possible.

[0110] (Grading)

[0111] The dried boron nitride powder may be crushed and then subjected to coarse particle removal by sieving or the like, and fine powder removal by air flow classification or the like, as necessary.

[0112] By the above method, the hexagonal boron nitride powder of the present invention containing specific hexagonal boron nitride can be obtained. In addition, the obtained hexagonal boron nitride powder is preferably subjected to classification treatment such as removal of coarse particles, removal of fine powder by air flow classification, wet classification, etc. as needed to prepare a hexagonal boron nitride powder with an increased content ratio of specific hexagonal boron nitride aggregate particles. The above classification treatment is particularly preferably dry sieve classification treatment, and the aperture is preferably 30 to 90 μm.

[0113] (Application of Boron Nitride Powder)

[0114] The use of the boron nitride powder of the present invention is not particularly limited, and can be applied to known uses without particular restrictions. If examples are used for suitable uses, the use as a filler in a resin for the purpose of improving electrical insulation, imparting thermal conductivity, etc. can be cited. In the use of the above-mentioned boron nitride powder, the obtained resin composition has high electrical insulation and thermal conductivity. In particular, in the use of the powder containing the above-mentioned specific boron nitride aggregated particles, the obtained resin composition has both high thermal conductivity and high electrical insulation with a dielectric strength of more than 80kV / mm.

[0115] The resin composition of the present invention can be used for known purposes without limitation, but by being mixed with the resin described later to form a thermally conductive resin composition or a thermally conductive molded body, it can be preferably used for thermally conductive interface materials such as polymer-based heat sinks and phase change sheets, heat dissipation tapes, heat dissipation greases, heat dissipation adhesives, caulking agents and other organic heat sinks, heat dissipation paints, heat dissipation coatings and other heat dissipation coatings, heat dissipation resin substrates such as PWB base resin substrates and CCL base resin substrates, insulation layers of metal base substrates such as aluminum base substrates and copper base substrates, sealing materials for power devices, interlayer insulating films and the like.

[0116] Furthermore, when the boron nitride powder of the present invention is prepared into a resin composition, it can be used by mixing with a thermally conductive filler such as aluminum nitride and alumina, which is a common high thermal conductive insulating filler.

[0117] Examples of the resin include thermoplastic resins such as polyolefins, vinyl chloride resins, methyl methacrylate resins, nylons, and fluororesins, thermosetting resins such as epoxy resins, phenolic resins, urea resins, melamine resins, unsaturated polyester resins, silicone resins, and bismaleimide triazine resins, fluororesins, liquid crystal polymers, and synthetic rubbers.

[0118] In addition, the above-mentioned resin combination may contain known additives such as known polymerization initiators, curing agents, polymerization inhibitors, polymerization delay agents, coupling agents, plasticizers, ultraviolet light absorbers, pigments, dyes, antibacterial agents, organic fillers, organic-inorganic composite fillers as compounding agents of the resin combination as required. In addition, other inorganic fillers may also be included within the scope of not damaging the effect of the present invention.

[0119] In addition, the boron nitride powder of the present invention can also be used as a raw material for boron nitride processed products such as cubic boron nitride and boron nitride molded products, a nucleating agent in engineering plastics, a phase change material, a solid or liquid thermal conductive interface material, a mold release agent for molten metal or molten glass molding, cosmetics, composite ceramic raw materials, etc.

[0120] Example

[0121] Hereinafter, the present invention will be described in further detail based on Examples, but the present invention is not limited to these Examples.

[0122] It should be noted that in the examples, each measurement is a value measured according to the following method.

[0123] [Pore volume-based median diameter (μm)] and [Volume of pores smaller than 3 μm (cm 3 / g)]

[0124] The pore volume-based median particle size (D1) of the obtained specific hexagonal boron nitride aggregate particles and hexagonal boron nitride powder was measured by mercury intrusion. The median particle size was calculated from the cumulative pore distribution obtained by plotting the pore size on the horizontal axis and the cumulative pore volume on the vertical axis when the pore distribution of 0.0036 μm to 200 μm was obtained. The Autopore IV 9520 manufactured by Micromeritics was used for calculation.

[0125] [Particle size D2 (μm) at 50% cumulative volume frequency of particle size distribution of hexagonal boron nitride powder]

[0126] For the obtained hexagonal boron nitride powder, the particle size (D2) at which the cumulative volume frequency of the particle size distribution is 50% is measured using LA-950V2 manufactured by HORIBA. The particle size distribution of the hexagonal boron nitride powder is measured using a particle size distribution measuring device MT3000 manufactured by Nikkiso Co., Ltd. It should be noted that the measurement sample is prepared according to the method shown below. First, 20 g of ethanol is added to a 50 mL screw-capped tube bottle as a dispersion medium, and 1 g of hexagonal boron nitride powder is dispersed in ethanol. The particle size at which the cumulative volume frequency of the obtained particle size distribution is 50% is taken as (D2).

[0127] [Oil absorption of hexagonal boron nitride powder according to JIS K5101-13-1:2004]

[0128] The oil absorption of the obtained hexagonal boron nitride powder was determined based on the procedure described in JIS K5101-13-1:2004 ("Testing Methods for Pigments" - Part 13: Oil Absorption - Section 1: Purified Linseed Oil Method).

[0129] [Specific surface area of ​​hexagonal boron nitride powder (m 2 / g)]

[0130] The specific surface area of ​​the obtained hexagonal boron nitride powder was measured using Macsorb HM model-1201 manufactured by Mountech Corporation.

[0131] [Concentration of impurity elements in hexagonal boron nitride powder (mass %)]

[0132] The concentration of impurity elements (calcium, magnesium, sodium, aluminum, lithium, strontium, iron, sulfur, nickel, chromium, manganese, silicon, phosphorus, titanium, barium, and cobalt) in the obtained hexagonal boron nitride powder was measured using ZSX Primus2 (trade name) manufactured by Rigaku Corporation.

[0133] Example A1

[0134] 195 g of boron oxide with a residual component of 2.1% by mass on a 425 μm sieve, 99 g of carbon black, and 55.2 g of calcium carbonate were mixed using a precision mixer. The (B / C) element ratio of the mixture was 0.68, and the CaO-converted mass content ratio of the oxygen-containing boron compound and the carbon source relative to 100 parts by mass of the total amount of B2O3 and C-converted mass of the above-mentioned oxygen-containing calcium compound was 10.5 parts by mass. 1500 g of the mixture was maintained at 1500° C. for 6 hours and at 1940° C. for 4 hours in a nitrogen atmosphere using a graphite Martin furnace to perform nitriding treatment.

[0135] Next, the boron nitride containing by-products was crushed and put into a container, and hydrochloric acid (7 mass % HCl) of 5 times the amount of the boron nitride containing by-products was added, and stirred at a Three-One Motor speed of 350rpm for 24 hours. After the acid wash, the acid was filtered, and the boron nitride obtained by filtration was dispersed in pure water equal to the amount of the used acid, and filtered again. This operation was repeated until the filtered aqueous solution became neutral, and then vacuum dried at 200°C for 12 hours.

[0136] The powder obtained after drying was passed through a sieve with an aperture of 90 μm to obtain a white hexagonal boron nitride powder. The physical properties of the obtained hexagonal boron nitride powder were measured by the above-mentioned method and are shown in Tables 1 and 2.

[0137] Example A2

[0138] The same method as in Example A1 was used except that the residual content of boron oxide on a 425 μm sieve was 2.9 mass %, the (B / C) element ratio was 0.72, and the CaO conversion mass content ratio of the oxygen-containing calcium compound relative to 100 mass parts of the total mass of B2O3 and C conversion of the oxygen-containing boron compound and the carbon source was 8 mass parts. The conditions and measured values ​​are shown in Tables 1 and 2.

[0139] Example A3

[0140] The same method as in Example A1 was used except that the residual content of boron oxide on a 425 μm sieve was 1.0 mass %, the (B / C) element ratio was 0.65, and the CaO conversion mass content ratio of the oxygen-containing calcium compound to 100 mass parts of the total mass of B2O3 and C conversion of the oxygen-containing boron compound and the carbon source was 6 mass parts. The conditions and measured values ​​are shown in Tables 1 and 2.

[0141] Example A4

[0142] The same procedures as in Example A1 were performed except that the 425 μm sieve residue of boron oxide was 0.1 mass % and the 300 μm sieve residue was 15.0 mass %.

[0143] Example A5

[0144] The same method as in Example A1 was used except that the residual content of the boron oxide on the 425 μm sieve was 0.5 mass %, the (B / C) element ratio was 0.70, and the CaO conversion mass content ratio of the oxygen-containing calcium compound relative to 100 mass parts of the total mass conversion of B2O3 and C of the oxygen-containing boron compound and carbon source was 8 mass parts. In addition, the obtained boron nitride powder was subjected to the above-mentioned 45 μm sieve treatment to prepare a sample in which the specific hexagonal boron nitride aggregate particle ratio was increased to 52%. The measured values ​​are shown in Tables 1 and 2.

[0145] Comparative Examples A1 to A6

[0146] The conditions and the parts shown in Table 1 were changed, and the same as Example A1 was used except that the conditions and the measured values ​​are shown in Tables 1 and 2. The hexagonal boron nitride powder produced in Comparative Example A2 does not contain the hexagonal boron nitride aggregated particles belonging to the present invention. The hexagonal boron nitride powder produced in Comparative Example A6 is not a white powder, a part of carbon remains, a black part is confirmed, and the analysis of the powder properties is not performed.

[0147] [Resin composition]

[0148] The boron nitride powder obtained in the above-mentioned Examples A1 to A6 is filled into epoxy resin to prepare a resin composition, and the thermal conductivity is evaluated. The epoxy resin is prepared as a mixture of 100 parts by mass of (JER828 manufactured by Mitsubishi Chemical Corporation) and 5 parts by mass of a curing agent (imidazole curing agent, CUREZOL 2E4MZ manufactured by Shikoku Chemical Co., Ltd.) and 210 parts by mass of methyl ethyl ketone as a solvent. Then, the varnish-like mixture and the hexagonal boron nitride powder are mixed in a rotation and revolution mixer (MAZERUSTAR manufactured by Kurabo Industries, Ltd.) in such a manner that the base resin becomes 35% by volume and the boron nitride powder obtained in the above-mentioned Examples A1 to A6 becomes 65% by volume to obtain a resin composition.

[0149] The above resin composition was coated on a PET film to a thickness of about 250 to 300 μm using an automatic coating machine PI-1210 manufactured by TESTER SANGYO CO,.LTD. and dried, and cured under reduced pressure, temperature: 200°C, pressure: 5 MPa, and holding time: 30 minutes to produce a sheet with a thickness of 220 μm. The sheet was analyzed in a temperature wave thermal analysis device, and the thermal conductivity was calculated. The results are shown in Table 3. The thermal conductivity of the sheet filled with the hexagonal boron nitride powder manufactured in Examples 1 to 5 is 8.5 W / m·K or more, indicating a high thermal conductivity. In addition, the dielectric strength was measured in a withstand voltage tester (manufactured by Tama Denso Co., Ltd.), and the result was a high dielectric strength of more than 80 kV / mm, suggesting that the amount of large pores in the resin composition that cause the reduction in dielectric strength is small.

[0150] In addition, the actual density is calculated based on the volume and weight of the produced sheet, and the actual density / theoretical density of the sheet when the theoretical density of the sheet calculated based on the filling rate of the resin and the hexagonal boron nitride particles is set to 100% is calculated as the relative density of the resin sheet. The actual density / theoretical density of the resin sheet produced by the hexagonal boron nitride powder of the present invention is 89 to 97%, and it can be seen that there are tiny pores in the resin sheet that do not reduce the thermal conductivity and dielectric strength. Therefore, by using the hexagonal boron nitride powder of the present invention, it is possible to achieve lightweight inorganic filled resin sheets while maintaining high thermal conductivity and dielectric strength.

[0151] In addition, the above resin compositions were obtained in the same manner except that the boron nitride powder obtained in Comparative Examples A1 to A5 was used, and the thermal conductivity, dielectric strength, and resin sheet relative density were measured and shown in Table 3. As can be seen from the table, the sheets filled with the boron nitride powder obtained in Comparative Examples A1 to A5 were unable to simultaneously achieve a thermal conductivity of 8.5 W / m·K, a dielectric strength of 80 kV / mm or more, and a resin sheet relative density of 97.0% or less.

[0152] [Table 1]

[0153] Table 1

[0154]

[0155] ※CaO equivalent weight parts per 100 weight parts of the total amount of boron compound (B2O3 equivalent) and carbon source (C equivalent)

[0156] [Table 2]

[0157] Table 2

[0158]

[0159] [Table 3]

[0160] Table 3

[0161]

[0162] Example B1

[0163] In the same manner as in Example A1, after reacting, acid washing, washing with pure water, and drying, the powder obtained after drying is applied to a sieve with an aperture of 45 μm to obtain a white hexagonal boron nitride powder containing specific hexagonal boron nitride aggregated particles. In the obtained hexagonal boron nitride powder, it was confirmed based on the SEM observation image with a magnification of 10,000 times that there are specific hexagonal boron nitride aggregated particles with a major diameter of 5 to 10 μm, a major diameter / minor diameter of 1.0 to 1.3, a circularity in the range of 0.3 to 0.8, and a maximum primary particle diameter of 4 μm or less that can be confirmed on the surface of the aggregated particles. The SEM image of the above-mentioned specific hexagonal boron nitride aggregated particles is as described above. Figure 1 As shown. In addition, the existence ratio of the specific hexagonal boron nitride aggregated particles calculated based on the area ratio of the 500-fold SEM observation image is 53%. In addition, for a particle near the average particle size of the obtained specific hexagonal boron nitride aggregated particles, the specific major diameter, major diameter / minor diameter, circularity, and the maximum diameter of the primary particle are shown in Table 4. Furthermore, the content of impurity elements of the specific hexagonal boron nitride aggregated particles specified by the measured values ​​of the obtained hexagonal boron nitride powder, the pore volume-based median particle size D1 (μm), and the pore volume (cm 3 / g) are shown in Table 4. In addition, the impurity element concentration was 40 ppm. The oxygen concentration was 0.2% and the carbon concentration was 0.01%.

[0164] [Mixing hexagonal boron nitride powder and resin composition]

[0165] With respect to 100 parts by mass of the boron nitride powder containing the specific hexagonal boron nitride aggregated particles thus produced, 5 parts by mass of hexagonal boron nitride powder containing commercially available hexagonal boron nitride single particles (wet particle size distribution D2 = 10 μm, average aspect ratio 10, impurity element concentration of 40 ppm, oxygen concentration of 0.2%, carbon concentration of 0.01%) were mixed to obtain a mixed hexagonal boron nitride powder. For the obtained mixed hexagonal boron nitride powder, the pore volume-based median particle size D1 (μm), the pore volume (cm2) of pores with a pore size of 3 μm or less, and the pore volume (cm3) of pores with a pore size of 1.5 μm or less were measured. 3 / g) and the particle size D2 (μm) at which the cumulative volume frequency of the wet particle size distribution is 50% are shown in Table 5.

[0166] The mixed hexagonal boron nitride powder is filled into epoxy resin to prepare a resin composition, and the thermal conductivity is evaluated. The epoxy resin is prepared as a mixture of 100 parts by mass of (JER828 manufactured by Mitsubishi Chemical Corporation) and 5 parts by mass of a curing agent (imidazole curing agent, CUREZOL 2E4MZ manufactured by Shikoku Chemical Co., Ltd.) and 210 parts by mass of methyl ethyl ketone as a solvent. Then, the varnish-like mixture and the hexagonal boron nitride powder are mixed in a rotation and revolution mixer (MAZERUSTAR manufactured by Kurabo Industries, Ltd.) in such a manner that the base resin becomes 35% by volume and the hexagonal boron nitride powder becomes 65% by volume to obtain a resin composition.

[0167] The resin composition was coated on a PET film to a thickness of about 250 to 300 μm using an automatic coating machine PI-1210 manufactured by TESTER SANGYO CO,.LTD. and dried, and cured under reduced pressure, temperature: 200°C, pressure: 5 MPa, and holding time: 30 minutes to produce a sheet with a thickness of 220 μm. The sheet was analyzed in a temperature wave thermal analysis device to calculate the thermal conductivity. In addition, the dielectric strength was measured in a withstand voltage tester (manufactured by Tama Denso Co., Ltd.). The results are shown in Table 5.

[0168] Example B2

[0169] The same conditions as in Example B1 were used except that the residual content of boron oxide on a 425 μm sieve was 2.8 mass %, the (B / C) element ratio was 0.73, and the CaO-converted mass content ratio of the oxygen-containing calcium compound relative to 100 mass parts of the total mass of B2O3 and C conversion of the oxygen-containing boron compound and carbon source was 8.2 mass parts. The conditions and measured values ​​are shown in Table 4. In addition, the impurity element concentration was 20 ppm. The oxygen concentration was 0.2% and the carbon concentration was 0.01%.

[0170] [Mixing hexagonal boron nitride powder and resin composition]

[0171] Using the boron nitride powder containing the specific hexagonal boron nitride aggregated particles thus produced, a mixed hexagonal boron nitride powder was prepared in the same manner as in Example B1, and then mixed with a resin to prepare a resin composition, and the thermal conductivity and dielectric strength were measured. The results are shown in Table 5.

[0172] Example B3

[0173] The same conditions as in Example B1 were used except that the residual content of boron oxide on a 425 μm sieve was 1.0 mass %, the (B / C) element ratio was 0.66, and the CaO-converted mass content ratio of the oxygen-containing calcium compound to 100 mass parts of the total mass of B2O3 and C-converted mass of the oxygen-containing boron compound and carbon source was 7 mass parts. The conditions and measured values ​​are shown in Table 4. In addition, the impurity element concentration was 20 ppm. The oxygen concentration was 0.2% and the carbon concentration was 0.01%.

[0174] [Mixing hexagonal boron nitride powder and resin composition]

[0175] Using the boron nitride powder containing the specific hexagonal boron nitride aggregated particles thus produced, a mixed hexagonal boron nitride powder was prepared in the same manner as in Example B1, and then mixed with a resin to prepare a resin composition, and the thermal conductivity and dielectric strength were measured. The results are shown in Table 5.

[0176] Example B4

[0177] The same conditions as in Example B1 were used except that the residual content on the 425 μm sieve of boron oxide was 0.1 mass % and the residual content on the 300 μm sieve was 15.0 mass %. The conditions and measured values ​​are shown in Table 4. In addition, the impurity element concentration was 20 ppm. The oxygen concentration was 0.2% and the carbon concentration was 0.01%.

[0178] [Mixing hexagonal boron nitride powder and resin composition]

[0179] Using the boron nitride powder containing the specific hexagonal boron nitride aggregated particles thus produced, a mixed hexagonal boron nitride powder was prepared in the same manner as in Example B1, and then mixed with a resin to prepare a resin composition, and the thermal conductivity and dielectric strength were measured. The results are shown in Table 5.

[0180] Example B5

[0181] The same method as in Example B1 was used except that the residual content of boron oxide on a 425 μm sieve was 0.5 mass %, the (B / C) element ratio was 0.70, and the CaO conversion mass content ratio of the oxygen-containing calcium compound relative to 100 mass parts of the total mass conversion of B2O3 and C of the oxygen-containing boron compound and carbon source was 8 mass parts. The measured values ​​are shown in Table 4. In addition, the impurity element concentration was 20 ppm. The oxygen concentration was 0.2% and the carbon concentration was 0.01%.

[0182] Example B6

[0183] With respect to 100 parts by mass of the boron nitride powder containing specific hexagonal boron nitride aggregated particles manufactured in Example B1, 15 parts by mass of hexagonal boron nitride powder containing commercially available hexagonal boron nitride single particles (wet particle size distribution D2 = 10 μm, average aspect ratio 10, impurity element concentration of 40 ppm, oxygen concentration of 0.2%, carbon concentration of 0.01%) were mixed to prepare a mixed hexagonal boron nitride powder, which was then mixed with a resin in the same manner as in Example B1 to prepare a resin composition, and the thermal conductivity and dielectric strength were measured. The results are shown in Table 5.

[0184] [Table 4]

[0185] Table 4

[0186]

[0187] [Table 5]

[0188] Table 5

[0189]

[0190] ※Content ratio of specific hexagonal boron nitride aggregate particles in mixed hexagonal boron nitride powder

[0191] As described above, the thermal conductivity of the sheets filled with the hexagonal boron nitride powder prepared in Examples B1 to B6 was 9.0 W / m·K or higher, indicating a high thermal conductivity. In addition, the high dielectric strength was 80 kV / mm or higher, suggesting that the amount of large pores that cause the decrease in dielectric strength in the resin composition was small.

[0192] It should be noted that, as a comparison object, agglomerated particles having a primary particle size of 8 μm, D 50 Commercially available hexagonal boron nitride powder with a particle size of 25 μm was used instead of the specific hexagonal boron nitride aggregate particles of Example B1. A mixed hexagonal boron nitride powder was prepared in the same manner as in Example B1, and a resin composition was made using the mixed hexagonal boron nitride powder. Various tests were carried out, and the results showed that the thermal conductivity was 8.8 W / m·K and the dielectric strength was as low as 65 kV / mm.

Claims

1. A hexagonal boron nitride powder, characterized in that: The hexagonal boron nitride powder contains hexagonal boron nitride aggregated particles at a ratio of 5% or more, wherein the major diameter of the hexagonal boron nitride aggregated particles is 5 to 10 μm, the major diameter / minor diameter is 1.0 to 1.3, the circularity is in the range of 0.3 to 0.8, and the maximum diameter of the primary particles that can be confirmed on the surface of the aggregated particles by SEM observation images with a magnification of 10,000 times is 4 μm or less, and the particle size distribution of the hexagonal boron nitride powder measured by a wet laser diffraction particle size distribution method has a cumulative volume frequency of 50%. 50 The particle size is 5 to 150 μm, the volume-based median diameter of pores measured by mercury intrusion porosimetry is 3.0 μm or less, and the content of impurity elements is 500 ppm or less.

2. The hexagonal boron nitride powder according to claim 1, wherein the BET specific surface area is 2 to 13 m 2 / g, oil absorption is 60~150cc / 100g. A resin composition comprising the hexagonal boron nitride powder according to claim 1 . A resin sheet formed from the resin composition according to claim 3. The resin sheet according to claim 4 , which has a dielectric strength of 80 kV / mm or more.

Citation Information

Patent Citations

  • Primary particle aggregate of hexagonal boron nitride, resin composition and application of the same

    JP2017165609A

  • Hexagonal boron nitride powder and method for producing same

    WO2018123571A1

  • Boron-nitride powder and resin composition containing same

    CN105026312A

  • Process for manufacturing boron nitride agglomerates

    CN109476480A